1992
DOI: 10.1128/iai.60.8.3339-3344.1992
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine model of disseminated trichosporonosis

Abstract: Serious infections caused by Trichosporon beigelii have been noted with increasing frequency in immunocompromised patients. Progress in understanding the pathogenesis of this emerging infection has been limited by the lack of an animal model. We developed a CF1 mouse intravenous inoculation model of disseminated trichosporonosis to evaluate the pathogenicity of T. beigelii in transiently immunosuppressed mice. Four inocula (1 X 106, 1 X 107, 2 x 107, and 4 x 107 CFU per animal) of one clinical strain of T. bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…DEX treatment of mice had a negligible effect on abscess induction by any of the oral treponemes. A report by Gokaslan and Anaissie (13) demonstrated that cyclophosphamide treatment of mice acutely decreased neutrophil numbers, which significantly increased the virulence of Trichosporon beigelii. Thus, we examined the effect of this immunosuppressive agent in altering the susceptibility of the host to infection with T. pectinovorum P2 as a representative of the oral treponemes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DEX treatment of mice had a negligible effect on abscess induction by any of the oral treponemes. A report by Gokaslan and Anaissie (13) demonstrated that cyclophosphamide treatment of mice acutely decreased neutrophil numbers, which significantly increased the virulence of Trichosporon beigelii. Thus, we examined the effect of this immunosuppressive agent in altering the susceptibility of the host to infection with T. pectinovorum P2 as a representative of the oral treponemes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The murine abscess model as originally described by Kastelein et al (19) and modified by Kesavalu et al (20)(21)(22)(23) was used to examine the virulence of the oral treponeme strains ( Table 1). Five to 10 mice per group were used, including the following: (i) normal mice, i.e., untreated mice challenged with viable treponemes (single injection per mouse); (ii) DEX mice, i.e., mice pretreated with dexamethasone (DEX, 40 g per animal; Fujisawa USA, Inc., Deerfield, Ill.) for 3 days prior to challenge infection, which has been shown to decrease neutrophil infiltration into sites of inflammatory lesions (45); and (iii) neutropenic mice, i.e., mice pretreated with cyclophosphamide (CYCL; Sigma) at a dose of 150 mg/kg of body weight 24 h before treponeme infection (13). For determination of virulence and abscess-forming capability, appropriate dilutions of bacteria in broth were made under anaerobic conditions.…”
Section: Analysis Of Enzymatic Activity the Levels Of Cell-associatementioning
confidence: 99%
“…Resistance to T. asahii infection was markedly lowered by CY. CY, a common agent used to obtain immunocompromised animal models (2,12,13,19,37,45), causes transient decreases in PMN, monocyte, and lymphocyte counts. The neutropenia in our CY model persisted for 6 days; however, most of the animals died after that period.…”
Section: Discussionmentioning
confidence: 99%
“…The neutropenia in our CY model persisted for 6 days; however, most of the animals died after that period. Thus, the initial host defense phenomena might be irretrievable, and reactions associated with migration of inflammatory cells upon recovery to sites of infection could have contributed to deterioration leading to death (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation